Common—Reading—Placing—Writing. (March 2023) - Badley, Graham Francis
I create here another sort-of-life text, a narrative in which I suggest ways in which we could or should practice human approaches to reading and writing. I patch together scraps recovered from the rubbish heap of my own personal and professional history.